Factors influencing employee retention among lecturers (a case of Kolej Universiti Poly-Tech Mara, Kuala Lumpur) - Nurul Hidayah, Aziz (2017)
The purpose of this study is to identify the factors influencing employee retention among lecturers at Kolej University PolyTech Mara. The factors that been investigated in this study are training and development, compensation and benefit, and leadership. This study involved survey of the lecturers at Kolej PolyTech Mara, Kuala Lumpur. A total of 120 questionnaires were distributed to the respondents and 114 questionnaires were returned and useable. The data was analysed by "Statistical Package for Social Science" (SPSS Window) Version 22.0. Correlation and multiple regression analysis were used to analyse the data. The findings found that there were relationship between the independent variables (training and development, compensation and benefit, and leadership) and the dependent variable (employee retention). The regression result indicated there were positive and significant relationships between training and development, compensation and benefit, and leadership with employee retention. This study also found the most dominant factor that influence the job retention and the factor was compensation and benefits.